Problems and current condition of tourism industry in the Tambov region - S. N. Moreva; S. E. Machalkin (Вестник Северо-Кавказского федерального университета)
Introduction. The article examines the regional aspects of tourism development in modern conditions based on the materials of the Tambov region, a region with the potential for growth in the ﬁeld of tourism and hospitality services.Goal. Identiﬁcation of problems and understanding of the actual condition of the tourism industry in the region, will allow to develop practical measures necessary to fulﬁll the objectives of the National Project "Tourism and Hospitality Industry".Materials and methods. The study is based on the analysis of statistical data from Rosstat, systematization of empirical and theoretical data presented in the electronic information environment, as well as the results of empirical research conducted by the authors.Results and discussion. The current state of tourism development in the Tambov region, demonstrate the positive dynamics of tourist ﬂow growth, which reﬂects the signiﬁcant changes in the industry and the rich potential of tourism resources in the region. The analysis of the competitive advantages of tourism in the Tambov region revealed the main problems, weaknesses and disadvantages, as well as potential development vectors and possible threats, which are reﬂected in the SWOT analysis.Conclusion. Based on the results of the study, the main problems that hinder the development of tourism in the Tambov region are identiﬁed: underdeveloped tourism infrastructure, lack of competitive tourist oﬀer, the image of the Tambov region as a region favorable for tourism has not been formed. Timely identiﬁcation of the problems of this region, determining the causes of these problems will allow to correct the shortcomings and realize the objectives of the National Project "Tourism and Hospitality Industry".